2018
DOI: 10.1007/s12032-018-1098-3
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of afatinib for patients aged 75 or older with advanced non-small cell lung cancer harboring EGFR mutations

Abstract: This phase I trial was conducted to determine the maximum tolerated dose (MTD) and recommended dose of afatinib for phase II trial in elderly patients with advanced non-small cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations. The study used a standard 3 + 3 dose escalation design. Patients aged 75 years or older with advanced NSCLC harboring EGFR mutations were enrolled. The doses of afatinib, which were given once daily, were planned as follows: level 1, 20 mg/day; level 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 23 publications
8
18
0
Order By: Relevance
“…Preferably, the patients with dose reduction showed even longer PFS than those without dose reduction. In our study, interstitial lung disease was observed in 5.7%, which was similar to the numbers in previous reports [21].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Preferably, the patients with dose reduction showed even longer PFS than those without dose reduction. In our study, interstitial lung disease was observed in 5.7%, which was similar to the numbers in previous reports [21].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we previously reported the phase I trial of afatinib for elderly patients (75 ≤). Although dose reduction rate of afatinib was high, the response rate was as high as 73.3% and PFS was 22 months (95% CI 13.1-not reached) [21].…”
Section: Discussionmentioning
confidence: 94%
“…Clinical activity of afatinib with respect to response and other e cacy outcomes (PFS and OS) was encouraging, consistent with other studies in elderly Japanese patients treated with afatinib in the same setting. 19,20 E cacy outcomes were also similar in patients with EGFR Del19-and L858R-postive tumours, as reported previously. 20 The safety pro le of afatinib was as expected from EGFR TKI treatment in elderly Japanese patients, 13,20,23 and was manageable with dose reductions.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we examined elderly patients aged ≥ 75 years (median [range] 77.5 [75-91] years); this has been identi ed previously as a relevant cut-off when considering the age at which more effective and tolerable therapies compared with chemotherapy are needed. 16,22 Baseline patient and disease characteristics were largely similar to those reported in two previous investigations of afatinib in 16 However, the frequency of patients with Del19-positive disease (61%) was slightly higher than reported in elderly patients in the other two Japanese studies (20% to 55%), 19,20 and in the LUX-Lung 7 subanalysis (37%). 16 Most patients (84%) in the current study had comorbidities, the most common being hypertension, and more than one third (34%) had baseline brain metastases.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation